Pemetaan Habitat Ruaya Benih Ikan Sidat (Anguilla bicolor) dan Potensinya di Pantai Selatan Jawa - Haryono Haryono; Gema Wahyudewantoro (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2016)
The eels is fish commodities that interesting and prospective for cultured. For the fish fry supply stillrely on catches of wild nature, one of them the south coast of Java. But the these habitat andabundance not yet to mapping The aims of this study to assess the conditions migration habitat ofglass eel, abundance, identification of threats, and conservation efforts. The study used surveymethods, glass eel catched with hand nets size 1 x 1 m, catching at night each 2 hours, thenumber of fisherman are three peoples. The results of the study recorded nine rivers and four ofthem potential as migration habitat of eels, habitat conditions are still good, the highest abundanceis Cibuniangen river in the rainy season, the daily abundance was fluctuated and the highest at3:00 a.m, identified several threats, conservation need integrated effort.Keywords: eels, habitat, abundance, conservation